Computational analysis of serum-derived extracellular vesicle miRNAs in juvenile sheep model of single stage Fontan procedure - Hyun-Ji Park; John M. Kelly; Jessica R. Hoffman; Felipe Takaesu; William Schwartzman; Anudari Ulziibayar; Takahiro Kitsuka; Eric Heuer; Asigul Yimit; Raphael Malbrue; Cole Anderson; Adrienne Morrison; et al. (Extracellular Vesicle)
Patients with single ventricle heart defects requires a series of staged open-heart procedures, termed Fontan palliation. However, while lifesaving, these operations are associated with significant morbidity and early mortality. The attendant complications are thought to arise in response to the abnormal hemodynamics induced by Fontan palliation, although the pathophysiology underlying these physicochemical changes in cardiovascular and other organs remain unknown. Here, we investigated the microRNA (miRNA) content in serum and serum-derived extracellular vesicles (EVs) by sequencing small RNAs from a physiologically relevant sheep model of the Fontan operation. The differential expression analysis identified the enriched miRNA clusters in (1) serum vs. serum-derived EVs and (2) pre-Fontan EVs vs. post-Fontan EVs. Metascape analysis showed that the overexpressed subset of EV miRNAs by Fontan procedure target liver-specific cells, underscoring a potentially important pathway involved in the liver dysfunction that occurs as a consequence of Fontan palliation. We also found that post-Fontan EV miRNAs were associated with senescence and cell death, whereas pre-Fontan EV miRNAs were associated with stem cell maintenance and epithelial-to-mesenchymal transition. This study shows great potential to identify novel circulating EV biomarkers from Fontan sheep serum that may be used for the diagnosis, prognosis, and therapeutics for patients that have undergone Fontan palliation.